Soybean Endo-1,3-Beta-Glucanase (GmGLU) Interaction With Soybean mosaic virus-Encoded P3 Protein May Contribute to the Intercelluar Movement - Shi, Feifei; Wang, Ying; Zhang, Fang; Yuan, Xingxing; Chen, Huatao; Chen, Xuehao; Chen, Xin; Cui, Xiaoyan (Frontiers in Genetics, 2020)
Soybean mosaic virus (SMV), a member of the genus Potyvirus, is a prevalent and devastating viral pathogen in soybean-growing regions worldwide. Potyvirus-encoded P3 protein is reported to participate in virus replication, movements, and pathogenesis. This study provides evidence that the soybean (Glycine max) endo-1,3-beta-glucanase protein (designated as GmGLU) interacts with SMV-P3 by using a yeast two-hybrid system to screen a soybean cDNA library. A bimolecular fluorescence complementation assay further confirmed the interaction, which occurred on the cytomembrane in Nicotiana benthamiana cells. Subcellular localization experiment indicated that GmGLU localized in cytomembrane and could co-localized at PD with PD marker. The transient expression of GmGLU promoted the coupling of Turnip mosaic virus replication and cell-to-cell movement in N. benthamiana. Meanwhile, qRT-PCR experiment demonstrated that the expression of GmGLU which involved in callose regulation increased under SMV infection. Under SMV infection, callose deposition at PD was observed obviously by staining with aniline blue, which raise a physical barrier restricting cell-to-cell movement of SMV. When overexpression the GmGLU into the leaves under SMV infection, the callose induced by SMV was degraded. Coexpression the GmGLU and SMV in soybean leaves, callose was not found, whereas a large amount of callose deposition on soybean leaves which were only under SMV infection. The results show that GmGLU can degrade the callose induced by SMV infection and indicate that GmGLU may be an essential host factor involvement in potyvirus infection.